DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON SMART APPS CREATOR TO IMPROVE MATH LEARNING OUTCOMES IN ELEMENTARY SCHOOL - Khairumnisa Putri Azizah; Erna Zumrotun; Wulan Sutriyani (Fakultas Keguruan dan Ilmu pendidikan (FKIP) Universitas Labuhan Batu, 2025)
This research aims to design interactive learning media using Smart Apps Creator, which is expected to improve students' mathematics learning outcomes regarding flat shapes. This study applies a Research and Development research approach using the ADDIE model as its methodology. This study involves 26 students in grade V from SDN 3 Mantingan as its subjects. The data collection techniques applied in this study include: 1) Results of material and media validation; 2) Questionnaires for teacher and student responses; 3) Learning outcome test questions in the form of multiple-choice pretest-posttest. Data analysis was conducted through the application of the N-gain tests and the paired sample t-test. The results of the study indicate that the product is rated as